Differential roles of PtdIns(4,5)P2 and phosphorylation in moesin activation during Drosophila development. - Roch, F.; Polesello, C.; Roubinet, C.; Martin, M.; Roy, C.; Valenti, P.; Carreno, S.; Mangeat, P.; Payre, F. (Journal of Cell Science, 2010)
The ezrin, radixin and moesin (ERM) proteins regulate cell membrane architecture in several cellular contexts. Current models propose that ERM activation requires a PtdIns(4,5)P(2)-induced conformational change, followed by phosphorylation of a conserved threonine. However, how these inputs contribute in vivo to orchestrate ERM activation is poorly understood. We addressed this issue by evaluating the contribution of PtdIns(4,5)P(2) and phosphorylation to the regulation of moesin during Drosophila development. Unexpectedly, we found that a form of moesin that cannot be phosphorylated displayed significant activity and could substitute for the endogenous product during wing morphogenesis. By contrast, we also show that PtdIns(4,5)P(2) binding is essential for moesin recruitment to the membrane and for its subsequent phosphorylation. Our data indicate that PtdIns(4,5)P(2) acts as a dosing mechanism that locally regulates ERM membrane recruitment and activation, whereas cycles of phosphorylation and dephosphorylation further control their activity once they have reached the cell cortex.